PENGARUH MEDIA GAMBAR BERSERI DALAM EDUGAME INTERACTY TERHADAP KREATIVITAS MENULIS PUISI SISWA KELAS V PADA MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR NEGERI GENTAN 01 KECAMATAN BENDOSARI KABUPATEN SUKOHARJO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of serial image media in the Interacty edugame on the poetry writing creativity of fifth-grade elementary school students. This research used a quantitative approach with a quasi-experimental design. The subjects consisted of 19 students in the experimental class and 16 students in the control class. Data were collected through performance tests in the form of poetry writing, administered as pretest and posttest. Data analysis included normality test, homogeneity test, and hypothesis testing using an independent sample t-test. The results showed that the average posttest score in the experimental class was higher (80.79) than the control class (74.06). The hypothesis test indicated a significance value of 0.016 < 0.05, meaning there was a significant effect of using serial image media in the Interacty edugame on students' poetry writing creativity. Thus, this media is effective in improving students' creativity in learning Indonesian language.